Вплив етиленгліколю на морфологію оксиду цинку, одержаного з цитратних розчинів - Romanova, I. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The course of decomposition of zinc oxide precursors with various amounts of citric acid and ethylene glycol has been investigated. It has been shown that ethylene glycol has a negative impact on the morphology of ZnO: the size of crystallites and percentage of big pores increases and the specific surface area decreases.